America Septentrionalis, concinnata juxta observationes Dñn Academiæ Regalis Scientiarum et nonnullorum aliorum, et juxta annotationes recentissimas - L'Isle, Guillaume de, 1675-1726; Lotter, Tobias Conrad, 1717-1777; Lotter, Georg Friedrich
This is a 1772 map of North America based upon De L'Isle's landmark map of 1700. It shows geographic places, settlements, islands, lakes, rivers, and tracks of a number of explorers routes along the west coast. Scale approximately 1:19,000,000. Relief shown pictorially. Hand colored. Includes summary (annotatio). In Latin. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .